(untitled) (Fiep Bulletin - online, 2014)
Considering pedagogical proposals that had been elaborated searching to breach with tecnicistas and mechanist models of the Physical Education, it came me it necessity and concern to search on the perspectives of the pupils of Physical Education, since they influence practical the pedagogical one of the professors of Physical Education, translating what the pupils consider important for its lives, what it makes direction, what this gift in its realities, what they wait of disciplines. The work searched to analyze the perspectives of the pupils on the importance of the Physical Education for its lives, being of qualitative nature and the descriptive type. Pupils of 8ª had participated of this study series of basic education, and of 1ª and 3ª series of the average education of the state school Filomena Scatena Christófano, pertaining to the Direction of Education of Presidente Prudente. The perspectives are understood as the result of the representation on the systemize knowledge and the experience of the pupils. The knowledge systemize constructed in the lessons frequented in the pertaining to school years and the experience in the school (in the lessons and the conviviality with the friends) and are of it (family and community). The emphasis given to the health as significant factor in the Physical Education, the present perspective greater in the answers of the pupils, is understood with certain promptitude, since the media emphasizes the practical one of the sport and the physical activity as promotional of the aesthetic health and the corporal one, relating with these ends venda of esportivos products. Therefore, the professor of Physical Education can launch hand of the knowledge gifts in the pupils and from constructing pedagogical practical its there, adaptando the systemize knowledge, gifts in literature, with the perspectives of its pupils, directing its work for the desvelamento of the knowledge, that is, allowing, endowing its pupils with the capacity to discern what it is important and necessary for its lives.